Inflammation and dysfunction in human aortic endothelial cells associated with poly‐l‐lactic acid degradation in vitro are alleviated by curcumin. Issue 12 (9th September 2019) - Chen, Dongping; Weng, Linsheng; Chen, Can; Zheng, Jian; Wu, Tim; Zeng, Sufen; Zhang, Suzhen; Xiao, Jianmin
Abstract: Poly‐l ‐lactic acid (PLLA) is widely used in clinic, for example, as biodegradable coronary artery stents. However, inflammatory responses in endothelial cells associated with PLLA degradation are relatively undefined. We previously reported inflammation in human aortic endothelial cells (HAEC) in vitro and in vivo. Here, we further assessed inflammatory injury, including cell migration, cell function, and inflammatory cytokines expressed in HAEC treated with PLLA and curcumin by CCK‐8, wound healing assay, ELISA, and Western blot. Significant inhibition of cell migration, remarkable dysfunction, and inflammatory responses were found in HAEC treated with PLLA degradation extract, and these effects were alleviated by Cur treatment. These findings indicated that cautious evaluation of biodegradable polymers should be performed, and Cur represents a promising anti‐inflammatory agent for alleviating endothelial dysfunction and inflammation caused by PLLA degradation. In addition, Cur should be further studied experimentally in in vivo experiments on animal models as a potential therapeutic to reduce thrombosis of biodegradable polymer stents.